2014
DOI: 10.1016/j.urols.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent urinary tract infections in healthy and nonpregnant women

Abstract: Recurrent urinary tract infections (RUTI) are prevalent and pose significant clinical challenges. Although the term RUTI has long been vaguely defined, a consensus definition has emerged in recent years. The exact etiology behind RUTI remains under debate, with valid arguments for both ascending reinfections as well as persistent infection inside the bladder. These persistent infections exist in the form of quiescent intracellular reservoirs in the mouse model and may represent a novel concept to explain UTI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 89 publications
(102 reference statements)
1
73
0
1
Order By: Relevance
“…Previous studies have shown that recurrent UTI can occur as a consequence of reinfection from persistent bacteria or reinitiation of infection from a fecal source (9). Fecal flora can serve as a UPEC reservoir for subsequent recolonization of the bladder (10).…”
mentioning
confidence: 99%
“…Previous studies have shown that recurrent UTI can occur as a consequence of reinfection from persistent bacteria or reinitiation of infection from a fecal source (9). Fecal flora can serve as a UPEC reservoir for subsequent recolonization of the bladder (10).…”
mentioning
confidence: 99%
“…Since T-cell responses can be severely hampered by prolonged and/ or repeated cognate antigenic exposure, 44,45 the activation difference could very well be a consequence of RUTI. In this regard, the presence of intracellular bacterial communities, which are known to be an important pathophysiological factor in RUTI, 46 could contribute to the frequent (re) stimulation of MAIT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since T‐cell responses can be severely hampered by prolonged and/or repeated cognate antigenic exposure, 44,45 the activation difference could very well be a consequence of RUTI. In this regard, the presence of intracellular bacterial communities, which are known to be an important pathophysiological factor in RUTI, 46 could contribute to the frequent (re)stimulation of MAIT cells.…”
Section: Discussionmentioning
confidence: 99%